The Six Right Principles of Drug Administration to Patients with Diabetes Mellitus in Hospitals: A Case Study - Afandi, Alfid Tri; Maula, Muthiatul; Asmaningrum, Nurfika; Putrha, Gede Dharmawan (Al-Hijrah Indonesia, 2024)
Background: About one-third of adverse events are drug-related medication administration errors (MAE). One method to improve drug administration safety is the application of the six rights of drug administration which include right patient, right drug, correct dose, right time, right route, and proper documentation. Nurses must apply it generously and nursing professional students must be able to use it well too. Purpose: The purpose of this case study is to compare the application of the six right medicine principles between nursing and nursing professional students to Mrs. E with Diabetes Mellitus in Hospital. Methods: This case study uses a quantitative study approach with a comparative descriptive design. Data were obtained through observation for seven days with an observation measuring instrument for applying the six correct drug administration are consist of 33 statements. Respondents were obtained from purposive sampling consisting of 7 Nursing Profession students at the Faculty of Nursing, University of Jember, and seven nurses at the Hospital. Results: The difference in applying the six right principles of drug administration to Mrs. E for seven days (14 shifts) by 11 students and nurses (4.8%). Conclusion: An indicator that still really needs to be improved by students and nurses is the true indicator of patients who are still below 50%. Meanwhile, the other indicators have achieved a total implementation of >70%.